The The Living Qur'an Approach as a Spiritual Therapy for the Recovery of People with Mental Disorders at Daarul Hakim Social Welfare Institution - Nidhom, Khoirun; Mualim, Mohamad (QiST: Journal of Quran and Tafseer Studies, 2025)
Mental health problems are an issue that is getting more and more attention in various parts of the world, including in Indonesia. Based on data from the Ministry of Health of the Republic of Indonesia, the prevalence of People with Mental Disorders (ODGJ) continues to increase every year. ODGJ, which includes individuals with severe mental disorders such as schizophrenia, requires not only medical care but also a holistic approach, including spiritual support. Although there are various studies on spiritual therapy, there are almost no studies that examine the implementation of Qur'anic therapy in the context of pesantren-based rehabilitation institutions in Indonesia, especially those that apply the concept of living Qur'an. This study aims to analyze and explain the implementation of Qur'anic verses as spiritual therapy for the recovery of ODGJ at the Daarul Hakim Social Welfare Institution in Sumber Village, Kradenan District, Blora Regency, which is a special Islamic boarding school for ODGJ that receives support from the Indonesian government. The results of the study show that the implementation of Qur'anic verses is realized through several forms of spiritual therapy, such as ruqyah syar'iyyah, recitation of certain surahs, dhikr, and structured religious assistance. These practices not only function as a method of spiritual healing, but also as a means of fostering inner peace, reducing psychological symptoms, and improving the self-control ability of ODGJ students. Thus, the application of Qur'anic verses as spiritual therapy has a significant contribution to the recovery process of ODGJ and is an important foundation to be studied further in the context of socio-religious institutions, filling the research gap related to the integration of Islamic spirituality in pesantren-based mental rehabilitation.